Nigerian Corruption, Good Governance, And Effective Leadership: Overcoming The Interface - Ajiteru,S.A.R; Sulaiman T.H; Abalaka, J.N (International Journal of Humanities and Social Sciences Reviews, 2025)
The purpose of the study was to assess how strong leadership affected Nigerian organizations' performance. A questionnaire and structured interview questions were used for the evaluation, which was intended to ascertain the effect of good leadership on the organization's performance; evaluating the impact of the relationship between effective leadership and organizational performance in fostering the maximization of the organization's objectives; determining whether there are any potential means of improving organizational performance; and analyzing whether there are three leadership barriers that impede organizational performance. The study looks at the chances of strong leadership in maintaining Nigeria's good governance. This acknowledges how the idea of "effectiveness" contributes to productivity in a certain polity. The study looks at leadership, corruption, and governance challenges using an eclectic approach and theories of the two public and nature of society. Its goal is to outline the course of an effective leadership and governance strategy that can solve Nigeria's several issues. As a result, everyone must work together to promote strong leadership and sound governance, which have the potential to eradicate corruption from the country's political system. The followers should also fulfill their civic obligations, both mandatory and voluntary.